The impact of a museum in a community – interferências 1.0 study case - Costa, Filipa Oliveira (2022)
This report covers the curricular internship from Porto Accounting and Business School’s Master degree in Intercultural Studies for Business. The internship was completed at Museu da Chapelaria, a museum located in the city of São João da Madeira. In today’s technologically evolved culture, museums may help connect what used to be to what has changed and will become. This means that museums put our society into perspective, and through new communication strategies such as digital transformation, they can create new ideas to stay relevant and unique. The digital transformation brought new work schedules and regulations to museums. Once they were closed due to the Covid-19 situation, remote work and digital promotion were essential. The market started a need for innovation and strategies to keep giving the public access to culture. Due to the public’s demand for immediate consumption, a museum’s ability to adapt to society's social and economic changes is valuable. In recent years, in response to growing market demand in the cultural sector, museums have been forced to use more attractive technological resources and, as a result, engage more effectively with the public. Thus, the use of marketing has emerged spontaneously in the development and increase of cultural offerings. Furthermore, museums are connecting even more with the community they are inserted in and the type of culture consumers they want to attract. The objective of this report is to present and analyze the internship at Museu da Chapelaria and portray in full detail the tasks carried out throughout the internship related to the museums and the project Interferências 1.0 (which promotes access to culture for more vulnerable groups in society), alluding to the new strategies that were created for the new type of work situation the world is living in.